Grigore Vieru in art (Confluenţe Bibliologice, 2024)
The article describes an exhibition organized in memory of the great national poet Grigore Vieru, hosted in the Reading Room for Psychopedagogical, Natural, and Exact Sciences, and Arts of the USARB Scientific Library. The exhibition features the most representative publications from the Library’s collections, showcasing both painted portraits of the poet and his works illustrated by the most renowned Bessarabian and Romanian artists.
Keywords: Grigore Vieru (1935-2009); bessarabian artists; book graphics